Pengembangan E-Modul Berbasis Model Discovery Learning untuk Meningkatkan Hasil Belajar Peserta Didik Kelas XI SMA Negeri 14 Makassar - Febrianti, Nur Fitriani Dwi; Sudding, Sudding; Danial, Muhammad (Chemistry Education Review (CER), 2023)
This study aims to develop a valid, practical, and effective E-module based on Discovery learning Model on Acid-Base learning materials, and to improve the learning outcomes. The study employed a 4D development model design which consisted of the define phase, the design phase, the develop phase, and the dissemination phase. The research subjects were 33 students of grade XI IPA 1 at SMAN 14 Makassar. The research used were 4 research results instruments, namely learning outcomes improvement instruments and product instruments such as validity instruments, practical instruments such as student response questionnaires and educator responses, and effectiveness instruments. The data collection technique used was giving pretests before being given treatment and giving posttests after being given treatment and giving questionnaires to assess the practicality of the E-module that had been developed. Data analysis used is N-Gain analysis for learning outcomes, validity, practicality, and effectiveness such as individual completeness, and class mastery percentage. The results of the analysis are: (1) The learning outcomes of class XI students at SMA Negeri 14 Makasar obtained an N-Gain value of 0.79 in the high category (2) The developed e-module obtained an average score of 89% categorized as high or very valid. (3) The practicality of the developed E-module obtained a score from the educator's questionnaire was 91% and the students were 87.24% categorized as very valid, and (4) The effectiveness of the results of the development of the E-module had an individual completeness score of 100% and class presentation completeness was 100%, so it was categorized as very successful or effective.